Fetal cells of mesenchymal origin in cultures derived from synovial tissue and skin of patients with rheumatoid arthritis - Hromadnikova, Ilona; Zlacka, Denisa; Hien Nguyen, Thi Thu; Sedlackova, Lucie; Zejskova, Lenka; Sosna, Antonin (Joint bone spine, 2008)
The transplacental cell transfer naturally takes place during pregnancy and occurs bi-directionally between the mother and fetus. Using real-time polymerase chain reaction (PCR) assay and sex determining region Y (SRY) gene as a marker, we examined the presence of male fetal cells in cell cultures derived from synovial tissues and skin dermis in women with prior pregnancy history suffering from rheumatoid arthritis (RA) who underwent synovectomy. Male DNA was detected in synovial cell samples derived from carpal, hip, metacarpophalangeal and metatarsophalangeal joints in five out of 13 (38.5%) patients with RA in a frequency range of 0.02-62.55 (mean 12.17) male cells per 10,000,000 total cells. SRY gene positivity was found as well in skin fibroblast cultures in four out of 10 (40.0%) RA patients in a frequency range of 3.26-43.47 (mean 15.42) male cells per 10,000,000 total cells, respectively. The difference in a frequency of fetal-derived male cells between both the cohorts did not achieve the statistical difference (p=0.77). We conclude that persisting male fetal cells are able to grow from non-inflamed tissues as well as from those which have many features characteristic of a stressed tissue. We conclude that persisting male fetal cells are also able to proliferate in cell culture since their presence was detected even in consecutive passages.
Keywords: Fetus; genetické markery; chimérismus; Male; Female; mladý dospělý; Synovectomy; Young Adult; revmatoidní artritida; fibroblasty; Genetic Markers; Sex-Determining Region Y Protein; mužské pohlaví; Mesoderm; kultivované buňky; ženské pohlaví; Adult; Arthritis, Rheumatoid; synovektomie; DNA; kůže; protein oblasti určující pohlaví na chromozomu Y; polymerázová řetězová reakce s reverzní transkripcí; Reverse Transcriptase Polymerase Chain Reaction; dospělí; plod; Skin; mezoderm; synoviální membrána; lidé; Humans; Fibroblasts; Cells, Cultured; Synovial Membrane; Chimerism